Agronomic performance of the selected Turkish grass pea (Lathyrus sativus L.) landraces - Basaran U.; Copur Dogrusoz M.; Gulumser E.; Mut H. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Eighteen selected Turkish landraces, one registered variety and four ICARDA origin genotypes of grass pea (Lathyrus sativus L.) were assessed for seed yield, protein ratio, 1000 seed weight and ODAP content in the Central Anatolian conditions under spring (2015) and autumn (2014) sowing. The effects of the genotype and sowing time were significant on the studied traits. Except protein ratio, investigated traits were higher among genotypes under autumn sowing. Seed yield varied from 101,90 to 187,31 kg/da, with a mean of 149,62 kg/da in spring sowing and was between 129,13 and 310,95 kg/da with a average of 205,85 kg/da in autumn sowing. Mean ODAP content of genotypes was 3.95 and 3.27 mg g-1 in autumn and spring sowing respectively. Many of the landraces were superior than registered variety in terms of the all the investigated traits in both sowing time. Especially higher seed yield and low ODAP content in the landraces is promising for developing new cultivars.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)